Method for improving the electrolyte wettability of dry-thickness electrode and electrode

CN122991969APending Publication Date: 2026-10-27GUIZHOU MEILING POWER SUPPLY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611028361.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该工艺路径存在固有缺陷:干粉料在热压过程中会发生高度致密化,导致最终成型的电极孔隙率偏低、孔隙结构曲折且连通性差

Benefits of technology

(1)提升浸润效率:根据Washburn渗透方程,液体在毛细管中自发的渗透深度与渗透所需时间的平方成正比。在传统干法厚电极中,电解液需要渗透的总深度非常大,这意味着,想要将厚电极完全浸润,所需的时间与难度都会急剧增加。而本发明通过将厚电极的“体相浸润”分解为薄膜的“单元浸润”,对于单个薄膜而言,电解液只需穿透较短的距离即可实现完全浸润,并且,电解液可以同时接触薄膜的上、下两个表面,液体可以从多个维度、多个点位同时向内部渗透,其浸润难度将大幅降低,浸润效率将大幅提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991969A_ABST
    Figure CN122991969A_ABST
Patent Text Reader

Abstract

The application discloses a method for improving the impregnation of dry-process thick electrode electrolyte, and belongs to the technical field of battery preparation. The method comprises the following steps: preparing multiple dry-process self-supporting electrode films with a thickness of 20-50 microns, respectively immersing the films into electrolyte for pre-impregnation treatment, and making the electrolyte fully occupy the pore network of each film; then, coating conductive glue solution on the surface of the pre-impregnated film, and performing lamination and hot pressing to obtain a pre-impregnated dry-process thick electrode with uniform internal electrolyte distribution. The method decomposes the "bulk impregnation" of the thick electrode into "unit impregnation" of the film, fundamentally realizes pre-impregnation and then lamination, greatly reduces the impregnation difficulty, avoids air lock and dry area, significantly improves the impregnation efficiency and uniformity, and effectively improves the discharge capacity and cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery manufacturing technology, specifically to a method and electrode for improving the electrolyte wettability of dry-process thick electrodes. Background Technology

[0002] Compared to traditional wet-process electrodes, novel dry-process electrode fabrication technology is widely regarded as one of the key technological paths for building next-generation high-performance battery systems due to its advantages such as eliminating the need for solvents, simpler process flow, environmental friendliness, and lower production costs. However, dry-process electrode fabrication technology, especially in the fabrication of thick electrodes, still faces significant technical bottlenecks that have not yet been overcome. Among these, poor electrolyte wettability is the core challenge restricting its industrial application.

[0003] Currently, the mainstream dry electrode fabrication process typically involves first fiberizing the binder, then mixing it with active materials and conductive agents to form a homogeneous dry powder, and finally hot-pressing it to create a self-supporting electrode. This process has inherent drawbacks: the dry powder undergoes high densification during hot pressing, resulting in a low porosity, a tortuous pore structure, and poor connectivity in the final electrode. Electrolyte wetting of the electrode relies primarily on capillary forces, penetrating from the electrode edge into the internal pores. This dense and tortuous porous structure of the dry electrode significantly increases the electrolyte penetration resistance. This problem is particularly pronounced in thick dry electrodes (typically >100 μm) designed to improve battery energy density. As the electrode thickness increases, the longitudinal penetration path of the electrolyte lengthens dramatically, and the internal penetration resistance increases exponentially, making it difficult for the electrolyte to effectively reach the electrode interior, easily forming large-scale, continuous unwetted "dry zones." The presence of these "dry zones" directly leads to low utilization of active materials, increased battery internal resistance, and a decrease in initial coulombic efficiency. More seriously, during battery cycling, the "dry zone" can trigger severe local polarization and side reactions, leading to lithium salt decomposition and gas production, which in turn severely affects the battery's rate performance and cycle life.

[0004] To alleviate the aforementioned electrolyte wetting problem, existing technologies typically employ the following strategies, but all have significant limitations: (1) Vacuum electrolyte injection technology: This is currently the most commonly used improvement method. Its principle is to remove air from the electrode gaps in a vacuum environment and use the negative pressure difference to promote the penetration of electrolyte into the gap structure. However, for high-density dry-process thick electrodes, the pores are narrow and in a closed or semi-closed state, and it is difficult to completely remove the air deep inside in a vacuum environment. Once the normal pressure is restored, the residual gas will still hinder the complete filling of electrolyte and cannot fundamentally eliminate the "dry zone". In addition, this process has high equipment requirements and will prolong the battery production cycle.

[0005] (2) Introduction of wetting agents: Wetting agents such as surfactants are added to the electrolyte to reduce its surface tension and improve its wettability to electrode materials. The disadvantage of this method is that the additives may be unstable within the electrochemical window, participate in side reactions, thereby affecting the cycle stability and safety of the battery, and causing irreversible capacity loss.

[0006] (3) Applying external pressure or ultrasonic assistance: After electrolyte injection, apply external mechanical pressure to the cell or use ultrasonic vibration to force electrolyte penetration. However, this method has limited effectiveness and may cause physical damage to the electrode structure, introducing additional safety risks and process complexity.

[0007] Furthermore, Korean Patent KR20220093603A discloses a dry electrode for secondary batteries, which has a self-supporting membrane formed on a current collector. This self-supporting membrane is composed of a fibrous composition impregnated with an electrolyte solvent, the composition comprising an active material, a conductive material, and a fibrous polymer binder. Although this approach improves ion conduction by pre-impregnating the self-supporting membrane with an electrolyte solvent, it essentially still involves molding the electrode as a whole before or during the impregnation process. The complete filling of the internal pores and elimination of "dry areas" in thick electrodes remain constrained by the dense structure, making it difficult to guarantee the uniformity and thoroughness of the overall impregnation of thick electrodes.

[0008] Despite numerous attempts to address the wetting challenges of dry-process thick electrodes, existing methods all adhere to the traditional process of "first forming the composite, then injecting electrolyte for wetting." Whether it's vacuum injection, adding wetting agents, or external aids, these methods essentially attempt to forcibly overcome inherent wetting defects after the electrode has already formed a dense, integral structure. This "post-natal" approach cannot fundamentally overcome the physical limitations imposed by the intrinsic structure of thick electrodes. It's like trying to forcefully fill a dense, thick sponge with water—inefficient and unlikely to achieve the desired results. Therefore, a new method is urgently needed that can fundamentally overcome these physical limitations and ensure efficient and effective electrolyte wetting of dry-process thick electrodes. Summary of the Invention

[0009] The purpose of this invention is to propose a novel "pre-wetting, then composite" process. Compared to the traditional approach of using various external methods to force the electrolyte to penetrate a thick, monolithic electrode, this invention proposes decomposing the thick monolith into multiple easily penetrated "units." After ensuring perfect electrolyte wetting at the unit level, these units are then composited into a whole. Specifically, multiple dry-process electrode films are prepared and thoroughly and rapidly wetted with electrolyte, ensuring that the electrolyte occupies the void network of each self-supporting film layer. These "pre-wetted" films are then composited into a dry-process thick electrode, thus ensuring the wetting efficiency and effectiveness of the electrolyte in the dry-process thick electrode.

[0010] The technical solution of the present invention: a method for improving the wettability of electrolyte in dry-process thick electrodes, comprising the following steps, Step 1: Prepare dry self-supporting films by dry mixing and stirring of electrode active materials, conductive agents and fiberizable binders to fiberize the fiberizable binders and obtain fiberized powder; hot press the fiberized powder to obtain multiple dry self-supporting electrode films with a thickness of 20μm~50μm. Step 2: Pre-wetting treatment. The multiple dry self-supporting electrode films obtained in Step 1 are immersed in the electrolyte and pre-wetting treatment is carried out under vacuum or pressure conditions to ensure that the electrolyte fully wets the pore network of each electrode film. Step 3: Prepare and coat the conductive adhesive solution. Dissolve the binder in an organic solvent, add the conductive agent and disperse evenly to obtain the conductive adhesive solution. The conductive agent accounts for 20% to 60% by mass, the binder accounts for 40% to 80% by mass, and the solid content of the adhesive solution is 10% to 20%. The conductive adhesive solution is evenly coated onto the surface of the dry self-supporting electrode film after the pre-wetting treatment in Step 2 by spraying or scraping. Step 4: Lamination and hot pressing. Multiple pre-wetting films coated with conductive adhesive are laminated and hot-pressed to obtain a pre-wetting dry-process thick electrode with uniform internal electrolyte distribution.

[0011] Further, in step 1, the electrode active material is lithium cobalt oxide, the conductive agent is conductive carbon black, the fiberizable binder is polytetrafluoroethylene powder, the proportion of the electrode active material is 80-98%, the stirring speed is 800 rpm-4000 rpm, and the stirring time is 5 min-30 min.

[0012] Furthermore, in step 2, the pre-impregnation treatment includes vacuum impregnation and pressure impregnation.

[0013] Furthermore, the vacuum degree of the vacuum impregnation is -80kPa to -100kPa, and the impregnation time is 2 to 10 hours.

[0014] Furthermore, the pressure for pressurized impregnation is 0.2 MPa to 1 MPa, and the impregnation time is 5 min to 60 min.

[0015] Furthermore, in step 3, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the conductive agent includes conductive carbon black and carbon nanotubes.

[0016] Furthermore, the rotation speed of the adhesive dissolving in the organic solvent is 1000 prm to 3000 prm, and the rotation speed of the conductive agent dissolving in the solvent is 1000 prm to 3000 prm.

[0017] Furthermore, the contact angle of the prepared dry-process thick electrode is <52.8°.

[0018] The beneficial effects of this invention are: (1) Improved wetting efficiency: According to the Washburn permeation equation, the spontaneous penetration depth of a liquid in a capillary is proportional to the square of the time required for penetration. In traditional dry-process thick electrodes, the total penetration depth required by the electrolyte is very large, which means that the time and difficulty required to completely wet the thick electrode will increase dramatically. However, this invention decomposes the "bulk phase wetting" of the thick electrode into the "unit wetting" of the thin film. For a single thin film, the electrolyte only needs to penetrate a short distance to achieve complete wetting. Furthermore, the electrolyte can contact both the upper and lower surfaces of the thin film simultaneously, and the liquid can penetrate into the interior from multiple dimensions and multiple points at the same time. The difficulty of wetting will be greatly reduced, and the wetting efficiency will be greatly improved.

[0019] (2) Avoiding the formation of "dry areas": In the traditional "composite first, then wetted" process, the electrolyte can only enter from the outer surface of the electrode. However, there are many tortuous and closed gaps inside the thick electrode. When the electrolyte enters, it compresses the air in these gaps into the electrode, forming "airlocks," which in turn lead to the formation of "dry areas" where the electrolyte cannot wet. This invention proposes to wet in the thin film state. The gap structure in the thin film state is mostly an "open structure," and gas can be freely replaced and discharged by the electrolyte from the upper and lower surfaces of the film. This allows the electrolyte to efficiently fill every gap under the drive of capillary force and external negative pressure, greatly reducing the formation of "airlocks" and "dry areas" inside the electrode. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the specific embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0021] Figure 1 This is a schematic diagram of the electrolyte wetting contact angle test according to an embodiment of the present invention; Figure 2 This is a schematic diagram of the electrolyte wetting contact angle test as a comparative example of the present invention. Figure 3 This is a schematic diagram comparing the discharge capacity of embodiments of the present invention with that of a comparative example; Figure 4 This is a schematic diagram comparing the cyclic test results of the embodiments and comparative examples of the present invention. Detailed Implementation

[0022] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. However, it should not be construed that the scope of the subject matter of the present invention is limited to the following embodiments. All modifications, substitutions and alterations made based on ordinary technical knowledge and common practices in the art without departing from the above-described technical concept of the present invention are included within the scope of the present invention.

[0023] A method for improving the wettability of electrolytes in dry-process thick electrodes includes the following steps: Step 1: Prepare dry self-supporting films. Using traditional dry electrode processes (including binder fiberization, dry powder mixing, rolling, etc.), prepare multiple thin self-supporting electrode films with good mechanical strength and consistency for either the positive or negative electrode. The thickness of the electrode films should be controlled between 20 μm and 50 μm. These electrode films will serve as the basic units for constructing the final dry thick electrode.

[0024] Step 2: Pre-wetting treatment. The multiple dry-process self-supporting films prepared in Step 1 are immersed in the electrolyte for wetting treatment. During the wetting process, auxiliary methods such as vacuum wetting or pressure wetting can be used to accelerate and ensure the wetting effect of the electrolyte.

[0025] Step 3: Prepare the conductive adhesive solution. Dissolve the binder (polyvinylidene fluoride) in an organic solvent (nitrogen-methylpyrrolidone) and disperse it evenly at a rotation speed of 1000~3000 prm. Then dissolve the conductive agent (conductive carbon black, carbon nanotubes, etc.) in the solvent and disperse it evenly at a rotation speed of 1000~3000 prm. The conductive agent accounts for 20%~60%, the binder accounts for 40%~80%, and the solid content of the adhesive solution is 10%~20%. Apply the prepared conductive adhesive solution evenly to the surface of the pre-wetted film prepared in Step 2 by spraying, scraping, or other methods. This coating will serve as a bridge for the interlayer bonding of the film.

[0026] Step 4: Multiple pre-wetted films coated with conductive adhesive are stacked and laminated using a hot-pressing device. During the hot-pressing process, the binder in the conductive adhesive undergoes cross-linking, firmly bonding adjacent films together through this functionalized interface. Simultaneously, the conductive agent in the adhesive forms a three-dimensional conductive network that runs through the multiple electrode layers. Ultimately, a pre-wetted dry-process thick electrode with uniform internal electrolyte distribution, strong interlayer bonding, and excellent electronic conductivity is formed.

[0027] Example: A dry mixer was used to uniformly mix the positive electrode material (lithium cobalt oxide), conductive agent (conductive carbon black), and binder (polytetrafluoroethylene powder) in a ratio of 94:3:3. The mixture was stirred at 3000 rpm for 5 minutes to achieve fiberization of the binder, resulting in a fiberized positive electrode powder. A hot press was used to press the fiberized positive electrode powder into four dry-process positive electrode films, with the film thickness controlled at 40 μm. The four prepared dry-process positive electrode films were then immersed in an electrolyte solution under vacuum for 2 hours at a vacuum level of -95 kPa.

[0028] A conductive adhesive was prepared by dissolving a binder (polyvinylidene fluoride) and a conductive agent (conductive carbon black) in an organic solvent (nitrogen-methylpyrrolidone). The mixture was dispersed uniformly at 1000 rpm, with the conductive agent comprising 50% of the composition, the binder 50%, and the adhesive having a solid content of 10%. The prepared conductive adhesive was then sprayed onto the surface of the impregnated film. Four films were stacked using a hot-pressing device and then hot-pressed with carbon-coated aluminum foil at a controlled temperature of 60°C to obtain a pre-impregnated dry-process positive electrode.

[0029] The prepared pre-wetting dry cathode was assembled with a lithium metal anode and a separator into a pouch cell, and then subjected to a second vacuum injection, with a standing time of 2 hours and a vacuum degree set to -95 kPa.

[0030] Comparative Example: A dry mixer was used to uniformly mix the positive electrode material (lithium cobalt oxide), conductive agent (conductive carbon black), and binder (polytetrafluoroethylene powder) in a 94:3:3 ratio. The mixture was stirred at 3000 rpm for 5 minutes to achieve fiberization of the binder, resulting in a fiberized positive electrode powder. The fiberized positive electrode powder was then pressed into a 160 μm thick dry-process positive electrode film using a hot press, and hot-pressed with carbon-coated aluminum foil to obtain a dry-process positive electrode. The composite dry-process positive electrode was then assembled with a lithium metal negative electrode and a separator into a pouch battery, and vacuum-filled with electrolyte, allowing it to stand for 8 hours at a vacuum level of -95 kPa.

[0031] The pouch cells prepared in the examples and comparative examples were subjected to formation, vacuuming, and other process steps, and their discharge capacity and charge-discharge cycle tests were performed. See details below. Figures 1-4 .

[0032] Reference Figure 1 and Figure 2 The electrolyte wetting test of the dry electrode film in the comparative example and the dry electrode film in the example is shown. It can be seen that the contact angle of the dry electrode film in the example is 52°, while the contact angle of the dry electrode film in the comparative example is 69°. This indicates that the dry electrode film has stronger hydrophilicity and is easier for the electrolyte to wet.

[0033] Reference Figure 3 The comparison shows the discharge capacity of the pouch cells prepared in the comparative example and the example. It can be seen that the discharge capacity of the battery prepared in the example is 1.62 Ah, while the discharge capacity of the battery prepared in the comparative example is 1.5 Ah. The battery prepared in the example can release a higher capacity, which may be because the electrolyte in the comparative example is not sufficiently wetted, and there are dry areas inside the electrodes, which prevents the capacity from being fully utilized.

[0034] Reference Figure 4 The example demonstrates a comparison of cycle tests between the pouch cells prepared in the embodiment and the comparative example. It can be seen that the battery prepared in the embodiment retains 89.97% of its capacity after 400 cycles, while the battery prepared in the comparative example retains 77.66% of its capacity after 400 cycles. This is because the electrolyte inside the electrode prepared in the embodiment is sufficiently and uniformly wetted, making it less prone to localized degradation during charge and discharge, thus affecting its cycle life. The method for improving the wettability of electrolyte in dry-process thick electrodes provided by the present invention has been described in detail above. Specific examples have been used to illustrate the structure and working principle of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principle of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for improving the wettability of electrolyte in dry-process thick electrodes, characterized in that: Includes the following steps, Step 1: Prepare a dry self-supporting film by dry mixing and stirring of electrode active material, conductive agent and fiberizable binder to fiberize the fiberizable binder and obtain fiberized powder. The fibrous powder is hot-pressed to obtain multiple dry self-supporting electrode films with a thickness of 20μm~50μm; Step 2: Pre-wetting treatment. The multiple dry self-supporting electrode films obtained in Step 1 are immersed in the electrolyte and pre-wetting treatment is carried out under vacuum or pressure conditions to ensure that the electrolyte fully wets the pore network of each electrode film. Step 3: Prepare and coat the conductive adhesive solution. Dissolve the binder in an organic solvent, add the conductive agent and disperse evenly to obtain the conductive adhesive solution. The conductive agent accounts for 20% to 60% by mass, the binder accounts for 40% to 80% by mass, and the solid content of the adhesive solution is 10% to 20%. The conductive adhesive solution is evenly coated onto the surface of the dry self-supporting electrode film after the pre-wetting treatment in Step 2 by spraying or scraping. Step 4: Lamination and hot pressing. Multiple pre-wetting films coated with conductive adhesive are laminated and hot-pressed to obtain a pre-wetting dry-process thick electrode with uniform internal electrolyte distribution.

2. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 1, characterized in that: In step 1, the electrode active material is lithium cobalt oxide, the conductive agent is conductive carbon black, the fiberizable binder is polytetrafluoroethylene powder, the proportion of the electrode active material is 80-98%, the stirring speed is 800 rpm-4000 rpm, and the stirring time is 5 min-30 min.

3. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 1, characterized in that: In step 2, the pre-impregnation treatment includes vacuum impregnation and pressure impregnation.

4. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 3, characterized in that: The vacuum degree of the vacuum impregnation is -80kPa to -100kPa, and the impregnation time is 2 to 10 hours.

5. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 3, characterized in that: The pressure for pressurized impregnation is 0.2 MPa to 1 MPa, and the impregnation time is 5 min to 60 min.

6. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 1, characterized in that: In step 3, the binder is polyvinylidene fluoride, the organic solvent is N-methylpyrrolidone, and the conductive agent includes conductive carbon black and carbon nanotubes.

7. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 6, characterized in that: The speed at which the adhesive is dissolved in the organic solvent is 1000 prm to 3000 prm, and the speed at which the conductive agent is dissolved in the solvent is 1000 prm to 3000 prm.

8. The method for improving the wettability of electrolyte in dry-process thick electrodes according to claim 1, characterized in that: The contact angle of the prepared dry-process thick electrode is <52.8°.